Aerosolized measles and measles-rubella vaccines induce better measles antibody booster responses than injected vaccines: randomized trials in Mexican schoolchildren - Bennett John V.; Fernandez de Castro Jorge; Valdespino-Gomez Jose Luis; Garcia-Garcia Ma de Lourdes; Islas-Romero Rocio; Echaniz-Aviles Gabriela; Jimenez-Corona Aida; Sepulveda-Amor Jaime (The World Health Organization, 2002)
OBJECTIVE: To compare antibody responses and side-effects of aerosolized and injected measles vaccines after revaccination of children enrolling in elementary schools. METHODS: Vaccines for measles (Edmonston-Zagreb) or measles-rubella (Edmonston-Zagreb with RA27/3) were given by aerosol or injection to four groups of children. An additional group received Schwarz measles vaccine by injection. These five groups received vaccines in usual standard titre doses. A sixth group received only 1000 plaque-forming units of Edmonston-Zagreb vaccine by aerosol. The groups were randomized by school. Concentrations of neutralizing antibodies were determined in blood specimens taken at baseline and four months after vaccination from randomized subgroups (n = 28-31) of children in each group. FINDINGS: After baseline antibody titres were controlled for, the frequencies of fourfold or greater increases in neutralizing antibodies did not differ significantly between the three groups that received vaccine by aerosol (range 52%-64%), but they were significantly higher than those for the three groups that received injected vaccine (range 4%-23%). Mean increases in titres and post-vaccination geometric mean titres paralleled these findings. Fewer side-effects were noted after aerosol than injection administration of vaccine. CONCLUSION: Immunogenicity of measles vaccine when administered by aerosol is superior to that when the vaccine is given by injection. This advantage persists with aerosolized doses less than or equal to one-fifth of usual injected doses. The efficacy and cost-effectiveness of measles vaccination by aerosol should be further evaluated in mass campaigns.